1979
DOI: 10.1128/aem.37.2.261-265.1979
|View full text |Cite
|
Sign up to set email alerts
|

Injury and recovery of Escherichia coli after sublethal acidification

Abstract: Over 99% of the viable cells of Escherichia coli K-12 were injured after a 60mi exposure to 0.3 M sodium acetate buffer at pH 4.2. Injured cells were those able to grow on Trypticase soy agar but unable to grow on violet red bile agar. The extent of both death and injury of acid-treated cells increased with decreasing pH or increasing concentration of acid. Injured cells were able to recover their colony-forming ability on violet red bile agar by incubation in Trypticase soy broth or potassium phosphate buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…Maintaining membrane permeable integrity is essential for maintaining the overall metabolism of a bacterial cell, hence, changes in the relative electrical conductivity on membrane integrity may severely hamper the cell metabolism, which may eventually lead to cell death (Cox et al 2001). Based on the above findings, it can be suggested that instant loss of membrane integrity and release of other essential nucleic acid components (260 nm materials and potassium ions) could be due to the hammering action of CFS of L. mesenteroides HJ69 that resulted in the significant antibacterial effect of treatment agent against the tested foodborne pathogens as also confirmed by previously (Roth and Keenan 1971;Przybylski and Witter 1979). TAJKARIMI, M., IBRAHIM, S. and CLIVER, D. 2010.…”
Section: Effect On Cell Membrane Permeabilitysupporting
confidence: 66%
“…Maintaining membrane permeable integrity is essential for maintaining the overall metabolism of a bacterial cell, hence, changes in the relative electrical conductivity on membrane integrity may severely hamper the cell metabolism, which may eventually lead to cell death (Cox et al 2001). Based on the above findings, it can be suggested that instant loss of membrane integrity and release of other essential nucleic acid components (260 nm materials and potassium ions) could be due to the hammering action of CFS of L. mesenteroides HJ69 that resulted in the significant antibacterial effect of treatment agent against the tested foodborne pathogens as also confirmed by previously (Roth and Keenan 1971;Przybylski and Witter 1979). TAJKARIMI, M., IBRAHIM, S. and CLIVER, D. 2010.…”
Section: Effect On Cell Membrane Permeabilitysupporting
confidence: 66%
“…Although leakage of cytoplasmic contents could have been prevented by their coagulation (Hugo & Longworth 1965), the T E M images of the cytoplasm of acid-treated cells suggested that this was not the case. Similarly, limited release of protein into the suspending medium was observed for Salmonella barielly incubated with 0.2 N acetic acid at pH 3.05 (Blankenship 1981) and Przybylski & Witter (1979) were unable to detect 26&180 nm absorbing material in the supernatant of cultures of E. colt K12 incubated with 0.3 mol/l sodium acetate buffer at p H 4-2. However, Statham & McMeekin (1988) found that potassium sorbate (5%, pH 7.0) increased the hydrophobicity of Altermonas putrifaciens cell wall which predisposed cells to lysis in the presence of lyzozyme.…”
Section: Discussionmentioning
confidence: 84%
“…The mode of action of SCFAs as antibacterial agents has yet to be fully elucidated but there are reports that they may influence either cell structure or cell metabolism. For instance, acetate damages the outer membrane of enteric bacteria (Roth and Keenan 1971 ;Przybylski and Witter 1979 ;Blankenship 1981) while intact bacteria are more resistant to the action of SCFAs than either spheroplasts or protoplasts (Sheu et al 1972 ;Galbraith and Miller 1973). Damage to the outer membrane would impair a cell's ability to act as a permeability barrier, allowing harmful substances to come into contact with the cytoplasmic membrane, leading to leakage of cell contents (Blankenship 1981), although lysis of Gram-negative cells by SCFAs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…enteritidis PT4 cells remained culturable, since growth occurred after treatment with 500 mmol 1-' formic acid, although TEM showed plasmolysis and aggregation of nuclear material. Inhibition of growth by SCFAs may be reversible, since acetate treated cells ( < 100 mmol 1-', p H 4.2) transferred to fresh medium resume growth (Przybylski and Witter 1979;Blankenship 1981). Treatment with SCFAs may make the cell less susceptible to shrinkage as a result of fixation, possibly as a result of altered fatty acid and phospholipid composition.…”
mentioning
confidence: 99%